2016
DOI: 10.1161/strokeaha.116.012934
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Inhibits Matrix Metalloproteinase-9 Activation and Reduces Infarct Growth After Focal Cerebral Ischemia in Hyperglycemic Mice

Abstract: Background and Purpose-Admission hyperglycemia is an independent risk factor for poor outcome of ischemic stroke. Amelioration of hyperglycemia by insulin has not been shown to improve the poststroke outcome. Glucagonlike peptide 1 receptor agonists, which modulate glucose levels by stimulating insulin secretion, have been shown to exert cytoprotective effects by inhibiting inflammation and oxidative stress. This study aimed to evaluate whether the glucagon-like peptide 1 receptor agonist exendin-4 could reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…The timing of drug administration varied between studies. Eight studies administered GLP‐1RAs pre‐ischaemia , eight post‐ischaemia and four both pre‐ and post‐ischaemia . For the seven studies involving DPP‐4Is, one study applied the drugs pre‐ischaemia , one post‐ischaemia and five studies both pre‐ and post‐ischaemia .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of drug administration varied between studies. Eight studies administered GLP‐1RAs pre‐ischaemia , eight post‐ischaemia and four both pre‐ and post‐ischaemia . For the seven studies involving DPP‐4Is, one study applied the drugs pre‐ischaemia , one post‐ischaemia and five studies both pre‐ and post‐ischaemia .…”
Section: Resultsmentioning
confidence: 99%
“…Mouse (C57BL/6), rat (Sprague Dawley/Wistar/Wistar albino) and gerbil (Mongolian) animal models were used (n = 1766). Fifteen studies tested non‐diabetic animals , six used diabetic/hyperglycaemic animals , and six studies included both non‐diabetic and diabetic . Diabetes was induced by streptozotocin , high‐fat diet or genetically modified animal strains including db/db mice , Goto‐Kakizaki rats and hyperglycaemia induced by infusion of 50% dextrose .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning vascular remodelling and inflammation, Kuroki et al [86] observed that a single administration of exendin-4, 60 min. after cerebral ischaemia, decreases vascular inflammation in hyperglycaemic mice when compared with vehicle and insulin administration.…”
Section: Diabetes Mellitus and Vascular Dysfunctionmentioning
confidence: 99%
“…We previously demonstrated that the GLP-1R agonists exenatide and liraglutide had neuroprotective and neurotrophic effects in cell and animal models of ischemic stroke, traumatic brain injury, Parkinson's disease (PD), Alzheimer's disease (AD) and ALS (Li et al, 2009, Li et al, 2010a, Li et al, 2012, Salcedo et al, 2012, Eakin et al, 2013, Greig et al, 2014). These data, together with findings by other groups (Bassil et al ., 2014; Holscher 2014; Darsalia et al, 2015; Athauda & Foltynie 2016 and Kuroki et al, 2016), suggest that incretin- based anti-diabetic drugs are neuroprotective and hold promise for repurposing as a treatment strategy for neurodegeneration. Positive pre-clinical data on these compounds has led to several ongoing clinical trials, such as a recent successful open label clinical trial of exenatide in Parkinson's disease patients (Aviles-Olmos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%